2005
DOI: 10.1016/j.ymthe.2005.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary and intramyocardial gene transfer in rhesus monkeys (Macaca mulatta): Safety and efficiency of HIV-1-derived lentiviral vectors for fetal gene delivery

Abstract: Fetal gene transfer was studied using intrapulmonary and intramyocardial transfer of SIN HIV-1-derived lentiviral vectors expressing EGFP in rhesus monkeys. Fetuses were monitored sonographically during gestation and tissue analyses performed at term or 3 months postnatal age. Animals remained healthy during the study period as evidenced by normal growth, development, hematology, clinical chemistry, echocardiography, and pulmonary function tests. Strong pulmonary fluorescence was observed postnatally after fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 42 publications
2
59
0
Order By: Relevance
“…5 Studies have also shown the efficiency of lentiviral vector-mediated gene transfer in fetal monkeys using both systemic and organ-targeting approaches. [6][7][8][9] These studies have indicated that intraperitoneal (i.p.) administration of reporter genes (e.g., enhanced green fluorescent protein [eGFP] or firefly luciferase) in early gestation results in long-term transgene expression in the muscular component of the diaphragm and peritoneum.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies have also shown the efficiency of lentiviral vector-mediated gene transfer in fetal monkeys using both systemic and organ-targeting approaches. [6][7][8][9] These studies have indicated that intraperitoneal (i.p.) administration of reporter genes (e.g., enhanced green fluorescent protein [eGFP] or firefly luciferase) in early gestation results in long-term transgene expression in the muscular component of the diaphragm and peritoneum.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HIV-1-based lentiviral vectors (LVs) have increased packaging capacity (optimal transgene insert B5-7 Kb 23 ) and, following in utero delivery, are able to integrate into the host genome to provide life-long stable transgene expression. 16,[24][25][26][27] Fetal lung gene transfer has been investigated in non-human primates, 20,28 rabbits, 29 rats 30,31 and sheep 32 using vesicular stomatitis virus glycoprotein (VSVg) pseudotyped LV. Long-term luciferase transgene expression (that is 12-15 months after fetal gene transfer) has been reported 31,33 although there is a paucity of quantitative information on degree of epithelial transduction and cell types transduced.…”
Section: Introductionmentioning
confidence: 99%
“…It was not surprising, therefore, when we examined other tissues of the recipients, to find that gene transfer was not limited to cells of the hematopoietic system, but had occurred in essentially all of the organs we examined, including numerous cell types within the liver, lung, and brain [79,81,82,86]. Concomitantly, in utero gene transfer studies performed by other investigators in sheep, rodent, and non-human primate models employing a variety of viral-based gene delivery vectors produced similar results [78][79][80][81][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], raising the exciting possibility that in utero gene therapy could potentially be used to treat not only hematologic disorders, but also numerous genetic disorders that affect tissues other than the hematopoietic system. For example, in the case of the hemophilias, this method could likely be used with success to delivering genes for the missing coagulation factors to the developing liver at levels that would covert patients with severe hemophilia to a moderate or even mild phenotype [79].…”
Section: Non-hematopoietic Tissuesmentioning
confidence: 86%